[Ulica Długa, kamienice nr 40/42] fot. Tadeusz Wański. - Wański, Tadeusz (1894-1958) (Tadeusz Wański HON EFIAP Art. Fotografik Z. P. A. F., 1953)
Przedstawia kamienice przy ul. Długiej 40.42, ok. 1953 r.